Surgical complications of cardiac implantable electronic devices: a systematic review and meta-analysis - Suárez-Paúl, Ignacio; Redondo-Castro, Belén; Gutiérrez Pastor, José M.; Membrive-Jiménez, María José; Caballero-Mateos, Antonio; Romero-Béjar, José Luis; Cañadas-De la Fuente, Guillermo A. (Frontiers in Cardiovascular Medicine, 2025)
AimTo identify the most common complications that occur after the implantation of a permanent pacemaker, and to estimate their prevalence. Method: systematic review and meta-analysis. Selection criteria: quantitative primary sources, written in English, no age restriction, published between 1 January 2018 and 1 March 2025. Information sources: This 30 systematic review is based on a search of the PubMed scientific database, using descriptors from the MESH thesaurus in the following search equation: “Pacemaker, artificial AND Surgery AND Postoperative complications”.Risk of biasStudies were assessed following the Mixed Methods Appraisal Tool (MMAT) guidelines. Results synthesis: descriptive analysis was used for the systematic review and random effects meta-analysis were performed.ResultsPacemaker implantation is a fairly common intervention, but it is not free of complications. The most frequent are pacemaker pocket infection, contusion or haematoma at the insertion site, painful shoulder and displacement of the generator or electrodes.ConclusionIt is important to take into account the patient's medical history and comorbidities, in order to match the device and its upkeep to the patient's characteristics, in order to minimise the risk of complications.